Unique Challenges for Mental Health in Inpatient Settings Amid the COVID-19 Pandemic - Sze Chet Lee; Chun Keat Ng; Mohd Amiruddin Mohd Kassim; Pang, Nicholas Tze Ping (2020)
COVID-19 has impacted the world in many ways due to fears of contracting the pandemic, social distancing, and large-scale movement control rules. These have especially grave consequences for inpatient psychiatry. This article reviews measures taken to adapt to the new norm in inpatient care, both for standalone psychiatry units and consultation-liaison units. For inpatient units, changes have been made for personal protective equipment usage, screening and triaging policies, and training and educational policies. Consultation liaison units together with inpatient units have been required to expand the scope of coverage and difficulties by providing certain teleconsultation services. As the new norm takes precedence, Sabah has to embrace and empower community-based psychiatry services for better outreach and coverage. This article discusses the issues underlying the new norm in the management of inpatient psychiatry patients in both units and presents some points and practical solutions on the ground to instil hope.